Variability of Different Yield Contributing Parameters and Yield of Some Okra (Abelmoschus esculentus) Accessions (Journal of Agriculture & Rural Development, 2008)
In order to assess the variability of yield contributing characters of 50 okra accessions and their interrelation effects on the yield of green pod a field experiment was undertaken at the Horticulture Farm of Bangladesh Agricultural University, Mymensingh during the period from February, 2002 to May, 2002. A wide range of variation was observed in case of weight of green pod per plant (105- 281g), days to first flowering (40-52days) and weight of individual green pod (14-26g). Moderate variation for length of green pod (12-19cm), number of green pods per plant (6-11) and yield of green pod (4-13 t/ha), lesser variation for percent of dry matter content (5-8%), number of ridges per green pod (5-9) and diameter of green pod (1-2cm) was observed. The highest genotypic coefficient of variation was observed in case of yield of green pod (GCV= 23.22%) followed by weight of green pod per plant (22.24%), weight of individual green pod (18.68%), number of ridges per green pod (13.49%), number of green pod per plant (10.84%), dry matter content of green pod (10.48%), diameter of green pod (6.90%) and length of green pod (6.24%). These characters suggested the existence of justifiable genetic distance among different cultivars. Correlation coefficient indicated that yield of green pod had highly significant positive association with weight of green pod per plant and weight of individual green pod. Path coefficient analysis showed that the weight of green pod per plant and weight of individual green pod were directly contributed towards the yield of green pod. Key words: Okra, accession, variability, yield.